110 The trigger project: introducing electronic patient reported outcome measures into radiotherapy services. (3rd November 2019) - Macnair, A; Sharkey, A; Le Calvez, K; Walters, R; Smith, L; Nelson, A; Staffurth, J; Williams, M; Bloomfield, D; Maher, J; ,
Abstract : Patients receiving pelvic radiotherapy can experience long term GI side effects post-radiotherapy. The Trigger project identifies patients experiencing symptoms of radiation-related bowel toxicity using the ALERT-B questionnaire, and directs them to the appropriate clinician. Trigger is a service evaluation project, aiming to prove the utility of electronic PROMs, and to demonstrate the feasibility of a low-resource project as a model for collecting PROMs. It is a collaboration between Macmillan Cancer Support, the Royal College of Radiologists, and three NHS Trusts: Velindre, Imperial College Healthcare and Brighton and Sussex University Hospitals. Patients register on the Trigger website, hosted by My Clinical Outcomes, and receive periodic emails to complete the short ALERT-B questionnaire electronically, to screen for long-term bowel symptoms which could have been caused by pelvic radiotherapy. If answering 'yes' to any of the questions, patients are directed to appropriate services. 6 months following the completion of their radiotherapy, patients are sent a separate questionnaire to evaluate the utility of the project. 336 patients registered in first the 9 months across the 3 sites. Patients with a range of different cancers signed up: anal (2%), bladder (1%), prostate (87%), rectal (4%) and gynaecological (6%). 43 patients (/65 (uptake 66%)) have answered their 6-month post treatment questionnaire, and 72% answered 'yes' to at least one of the ALERT-B questions. 85% of responding patients reported they found the Trigger project helpful. These promising results show that electronic PROMS can be introduced in radiotherapy departments using a low resource model. The Trigger project works as a feasibility model, showing patients engage with electronic PROMs projects, and find them useful. PROMs for other tumour types could be collected in a similar manner, based on the low-resource model used here, using site-specific PROMs based on the ALERT-B tool.